GPR10 gene deletion in mice increases basal neuronal activity, disturbs insulin sensitivity and alters lipid homeostasis - Pražienková, Veronika; Funda, Jiří; Pirník, Zdenko; Karnošová, Alena; Hrubá, Lucie; Kořínková, Lucia; Neprašová, Barbora; Janovská, Petra; Benzce, Michal; Kadlecová, Michaela; Blahoš, Jaroslav; Kopecký, Jan; et al. (Gene, 2021)
G-protein-coupled receptor GPR10 is expressed in brain areas regulating energy metabolism. In this study, the effects of GPR10 gene deficiency on energy homeostasis in mice of both sexes fed either standard chow or a high-fat diet (HFD) were studied, with a focus on neuronal activation of PrRP neurons, and adipose tissue and liver metabolism. GPR10 deficiency in males upregulated the phasic and tonic activity of PrRP neurons in the nucleus of the solitary tract. GPR10 knockout (KO) males on a standard diet displayed a higher body weight than their wild-type (WT) littermates due to an increase in adipose tissue mass; however, HFD feeding did not cause weight differences between genotypes. Expression of lipogenesis genes was suppressed in the subcutaneous adipose tissue of GPR10 KO males. In contrast, GPR10 KO females did not differ in body weight from their WT controls, but showed elevated expression of lipid metabolism genes in the liver and subcutaneous adipose tissue compared to WT controls. An attenuated non-esterified fatty acids change after glucose load compared to WT controls suggested a defect in insulin-mediated suppression of lipolysis in GPR10 KO females. Indirect calorimetry did not reveal any differences in energy expenditure among groups. In conclusion, deletion of GPR10 gene resulted in changes in lipid metabolism in mice of both sexes, however in different extent. An increase in adipose tissue mass observed in only GPR10 KO males may have been prevented in GPR10 KO females owing to a compensatory increase in the expression of metabolic genes.
Keywords: Female; Homeostasis; myši; Animals; myši knockoutované; Insulin Resistance; Neuronal activity; Standard and high-fat diets; GPR10 KO mice; mužské pohlaví; Energy Metabolism; Mice, Knockout; Obesity; Energy expenditure; Lipid Metabolism; hormon uvolňující prolaktin; myši inbrední C57BL; Prolactin-Releasing Hormone; inzulinová rezistence; Mice; zvířata; receptory spřažené s G-proteiny; energetický metabolismus; metabolismus lipidů; Mice, Inbred C57BL; ženské pohlaví; Receptors, G-Protein-Coupled; Prolactin-releasing peptide; obezita; homeostáza; Male; Gene expression